1556-1557 (H. 963-964) TARİHLİ DİVÂN-I HÜMÂYÛN RUÛS DEFTERİ (126-243) TRANSKRİPSİYON-DEĞERLENDİRME-DİZİN - KARABULUT, FATİH (Fırat Üniveristesi, 2015)
Tezimizi oluşturan Divân-ı Hümâyûn Ruûs Defteri, 1556-1557 tarihinde Osmanlı Devleti'nde beylerbeyi, sancakbeyi gibi devletin üst düzey yöneticilerinden en alt kademedeki görevlilere kadar yapılan atama ve azilleri içermektedir. Ayrıca has, zeamet ve tımarların dağıtımı, bedellerinin arttırılması veya azaltılması, idari görevlilerin emekliliğe ayrılması, usulsüzlük yapanların görevden alınması gibi birçok konuda buyruldu kayıtlarından oluşmuştur. Bu sebeple Osmanlı Devleti'nin idari, siyasi, sosyal, ekonomik ve kültür hayatı ile ilgili önemli bilgilere ulaşmak mümkündür. İlgili defterin 126-243. sayfaları arasındaki 931 buyruldunun transkripsiyonu yapılmıştır. Bunun yanı sıra yer ve şahıs adları dikkate alınarak metnin dizini hazırlanmış ve defterin verdiği bilgiler ışığında tablolar kullanılarak genel değerlendirmesi yapılmıştır. Anahtar Kelimeler: Osmanlı, Divân-ı Hümâyûn, Ruûs, Buyruldu, Atama

The Ruus book of imperial council of ottoman empire (dated on 1556- 1557), which is worked by us, includes different documents regarding assigment and deposing of civil cervants, who served different layers of the state adminstration, changing from upper most layer such as governor, governor of sanjak to low level civil servants. Furthermore it includes distributing of dynastical territory, fief, rising or reducing of their prices, retiring of civil servants, deposing of person who malpractice and other several subject as mentioned. Thus it is possible that we can reach to value informations about political, social, economical and cultural life of Ottoman Empire. İn the book, we made transcription of 931 order, which was located pages between 126- 243. Besides we made directory of the book by taking into account persons and places names. Finally according to the book we prepared several charts and by using it we made general evaluation of the book. Key Words: Ottoman, Imperial Council, Ruus, Order, Assignment
1556-1557 (h. 963-964) dated the Ruus Book of Imperial Council (p. 126-243) text- assessment- directory
Keywords: Tarih